Cass R. Sunstein, The Cost-Benefit Revolution, Cambridge: MIT Press, 2018, 288 pp. - Varela Castro, Samanta (Gestión y Política Pública, 2020)
Reseña al libro The Cost-Benefit Revolution de Cass R. Sunstein.